The oldest record of the family Iridinidae (Unionida): New fossil genera and species of bivalves from the Salvador Formation (Berriasian), Jatobá Basin, northeastern Brazil - Baumann, Débora Eliza [UNESP]; Simone, Luiz Ricardo L.; da Silva, Rafael Costa; Ghilardi, Renato Pirani [UNESP] (Elsevier, 2025)
Two new genera of freshwater bivalves from the family Iridinidae (Order Unionoida) are described, each including one new species: Duplexium jatobensis gen. et sp. nov. and Anhapoa munizi gen. et sp. nov. Duplexium gen. nov. is distinguished by possessing both heterodont and taxodont hinge dentition, while Anhapoa gen. nov. has a heterodont dentition with one tooth in the right valve and two teeth in the left valve. These fossils originate from the Salvador Formation (Late Berriasian, Cretaceous) in the Jatobá Basin, Pernambuco, Brazil, a region previously known only for its marine Devonian bivalves. The presence of African Iridinidae in Brazil and its implications for the evolution of regional unionoids are also discussed. Zoobank: urn:lsid:zoobank.org:pub:5FF797D8-0CDE-4CDD-83C9-8EB87E4367EB